2005
DOI: 10.1093/toxsci/kfi187
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Food Matrix on In Vivo Immune Responses to Purified Peanut Allergens

Abstract: There is little knowledge about the factors that determine the allergenicity of food proteins. One aspect that remains to be elucidated is the effect of the food matrix on immune responses to food proteins. To study the intrinsic immunogenicity of allergens and the influence of the food matrix, purified peanut allergens (Ara h 1, Ara h 2, Ara h 3, or Ara h 6) and a whole peanut extract (PE) were tested in the popliteal lymph node assay (PLNA) and in an oral model of peanut hypersensitivity. In the PLNA, peanut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 36 publications
3
62
1
1
Order By: Relevance
“…Our findings are in line with previous studies demonstrating that the matrix from allergen sources contains compounds that might aid allergic sensitization and lipids may play a fundamental role 1, 2, 3. The pro‐inflammatory mediators produced by KC upon PNL stimulation may perhaps lead to barrier disruption and promote the proper environment allowing Ara h 1 or Ara h 2 to penetrate the epidermis and recruit neighboring cells involved in the allergic sensitization process 6.…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are in line with previous studies demonstrating that the matrix from allergen sources contains compounds that might aid allergic sensitization and lipids may play a fundamental role 1, 2, 3. The pro‐inflammatory mediators produced by KC upon PNL stimulation may perhaps lead to barrier disruption and promote the proper environment allowing Ara h 1 or Ara h 2 to penetrate the epidermis and recruit neighboring cells involved in the allergic sensitization process 6.…”
Section: Figuresupporting
confidence: 91%
“…Exposure of infants to peanut oil‐containing lotions was described as a risk factor for the development of peanut allergy 1. There is evidence that only peanut extracts containing lipids were able to induce sensitization 2, 3. How this occurs at the molecular level is still unknown.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Both IL-4 and IFN-γ production as well as IgE, IgG1 and IgG2a were found at the very early phase of the response to peanuts. The same group also examined the role of cytotoxic T-lymphocyte associated antigen 4 (CTLA-4), a negative regulator of T cell activation, on peanut sensitization (Van Wijk et al, 2005b). The use of an antibody against CTLA-4 in a murine model of peanut allergy failed to elicit an allergen-specific response.…”
Section: Discussionmentioning
confidence: 99%
“…It was clearly shown that C3H/HeJ mice can be used in studies on induced anaphylaxis (IgE-mediated) and that its clinical course (T-and B-cells responses) was similar to that occurring in individuals with hypersensitivity to peanuts [Li et al, 2000]. Also other species of mice: BALB/c, DBA/2, A/J, BDF-1, C57B/6, are used in studying the mechanisms of food allergy [Ladics et [Pramod et al, 2007;van Wijk et al 2005]. In our studies, BALB/c mice were used to determine their utility in studies related to food reaction caused by peanut protein administration (crude extract).…”
Section: Introductionmentioning
confidence: 99%